Boganmeldelser - Madsen, Mikael Rask; Klette, Hans; Scherg, Rune H.; Holmberg, Lars; Garde, Peter; Clausen, Susanne; Nilsson, Roddy; Brydensholt, Hans Henrik; Havelund, Jonas (Nordisk Tidsskrift for Kriminalvidenskab, 2008)
Book reviews